2007
DOI: 10.3732/ajb.94.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Early ontogenetic patterns in chemical defense in Plantago (Plantaginaceae): genetic variation and trade‐offs

Abstract: Predictions based on the plant age and growth-differentiation balance hypotheses of defense were tested in two congeneric species, Plantago lanceolata and P. major, by quantifying iridoid glycosides, defensive chemicals, in seeds and leaves during the first 6 wk of growth. Concentrations decreased from the seed to 2-wk-old seedling stage in P. lanceolata, but increased during this period in P. major. In both species, levels were similar for 2- and 4-wk-old plants, then significantly increased from 4 to 6 wk. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 55 publications
4
63
1
2
Order By: Relevance
“…genetic variation due to varying selective pressures), that may be important drivers of variation in L. dalmatica allelochemistry. Other studies investigating plants containing iridoid glycosides have demonstrated that genetic, ontogenetic, biotic, and abiotic environmental variation can all influence these defense compounds Bowers and Stamp 1993;Adler et al 1995;Darrow and Bowers 1999;Marak et al 2002;Fuchs and Bowers 2004;Barton and Bowers 2006;Barton 2007;Wurst et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…genetic variation due to varying selective pressures), that may be important drivers of variation in L. dalmatica allelochemistry. Other studies investigating plants containing iridoid glycosides have demonstrated that genetic, ontogenetic, biotic, and abiotic environmental variation can all influence these defense compounds Bowers and Stamp 1993;Adler et al 1995;Darrow and Bowers 1999;Marak et al 2002;Fuchs and Bowers 2004;Barton and Bowers 2006;Barton 2007;Wurst et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the case of fungal endophytes, in which endophytic fungi produce their own compounds, AM fungi manipulate the defensive chemical concentrations already produced by P. lanceolata. Nevertheless, given the ubiquity of AM fungal infection in terrestrial communities, the influence of AM fungi on plant defense will likely also have important cascading effects through terrestrial ecosystems, especially given the lack of a trade-off between growth and constitutive defense in P. lanceolata (Barton 2007) and that induction of iridoid glycosides has been shown to have broad-spectrum effects against other plant antagonists (Biere et al 2004). While previous models demonstrate that mycorrhizal modification of plant defense can have profound effects on the dynamics of such plant-herbivore interactions (Bennett et al 2006), these models have not yet considered the implications of mycorrhizal modification of the induction of plant responses and do not scale up these potential effects through terrestrial food webs.…”
Section: S Calosporamentioning
confidence: 99%
“…Young plants are more heavily defended in some species (Bryant and JulkunenTiitto 1995), while older plants are more greatly defended in other species (Fritz et al 2001;Barton 2007;Goodger et al 2007). Surprisingly, relatively few studies have tested for age-specific costs (Barton 2007;Boege et al 2007). In one study, Barton (2007) tested for trade-offs between growth and iridoid glycoside production in two Plantago species, Plantago major and Plantago lanceolata.…”
Section: Introductionmentioning
confidence: 95%
“…Age-specific costs might also be expected because seedlings, saplings, and mature plants often differ dramatically in defenses (Briggs and Schultz 1990;Fritz et al 2001;van Dam et al 2001;Del Val and Dirzo 2003;Schaffner et al 2003;Albrectsen et al 2004;Fuchs and Bowers 2004;Barton 2007;Boege et al 2007;Goodger et al 2007;Elger et al 2009). Young plants are more heavily defended in some species (Bryant and JulkunenTiitto 1995), while older plants are more greatly defended in other species (Fritz et al 2001;Barton 2007;Goodger et al 2007).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation